A systematic review of multimodal analytical techniques for enhancing cyber resilience in smart cities - Ibrahim, Zul-Azri; Ismail, Saiful Adli; Abdul Rahim, Fiza (Universiti Teknologi MARA, Perak, 2025)
In recent years, the advancement of smart city technologies has necessitated a rethinking of urban resilience strategies, especially in the face of escalating cyber threats. Enhancing cyber resilience in smart cities is crucial due to their reliance on interconnected digital infrastructures that manage essential services such as transportation, energy, healthcare, and public safety. Cyber attacks on these systems can disrupt services, compromise data, and undermine public trust. This systematic review examines 27 selected articles on the application of multimodal analytical techniques to enhance the cyber resilience of smart cities. By evaluating these studies based on their analytical frameworks, techniques used, and research contexts, the researcher identifies the benefits and challenges of integrating multimodal data such as text, audio, video, and sensor data into urban cyber resilience strategies. The findings reveal that various multimodal strategies, including machine learning, data fusion, and realtime monitoring, significantly contribute to the robustness of smart urban infrastructures against cyber attacks. This review provides a comprehensive understanding of the application of multimodal analytics in safeguarding smart city infrastructures, highlighting best practices, technological advancements, and future research directions.